Telaah Atas Ilustrasi Buku Roesdi djeung Misnem sebagai Bacaan Murid-Murid Sekolah Rakyat di Jawa Barat sebelum Perang Dunia II - H.W. Setiawan; Irma Damajanti; Prijanto Sunarto (Journal of Visual Art and Design, 2007)
This essay is a preliminary study on a series of book illustrations by a Dutch illustrator, the late W.K. de Bruin (1871-1945), which was printed in the book of Roesdi djeung Misnem: Boekoe Batjaan pikeun Moerid di Sakola Soenda (Roesdi and Misnem: A Reading Book for Sundanese School Pupils). As indicated by the sub-title, the so called "Buku Rusdi" (Book of Rusdi), which was written in collaboration between Sundanese and Dutch authors, is a reading book for children at Sakola Ra'yat or SR (literally "School for the Folk"), elementary school in West Java "“ Indonesia before the World War II. At the time, it used Sundanese as a medium of instruction. Amid previous studies on the history of book illustration in Indonesia, this study is a humble effort to consider some fundamental questions on the way illustrator represents people in visual forms, mainly on how the Dutch illustrator depicted Sundanese childhood in the course of European colonialism in Indonesia at the beginning of the twentieth century.